High-temperature Néel skyrmions in Fe3GaTe2 stabilized by Fe intercalation into the van der Waals gap - Rana Saha; Holger L. Meyerheim; Börge Göbel; Ingrid Mertig; Stuart S. P. Parkin (npj Spintronics)
Abstract Two-dimensional (2D) van der Waals (vdW) magnets that exhibit ferromagnetism at ambient temperature show great promise for spintronic applications. However, until now, only a few pristine or doped 2D magnets have demonstrated the ability to host non-collinear spin textures, thereby limiting their potential applications. Here we directly observe Néel-type skyrmions in the metallic vdW magnetic compound Fe3GaTe2 (FGaT) up to temperatures well above room temperature (≈340 K) in the absence of any external magnetic field. We show that the presence of defects in the structure of FGaT make its structure acentric and therefore compatible with hosting skyrmions that would otherwise not be possible. Indeed, in this regard it is very similar to the closely related compound Fe3GeTe2 (FGT), whose structure with the same space group P3m1 is also realized by defects. Interestingly, however, FGaT accommodates a significantly higher concentration of Fe within the vdW gaps, likely accounting for its enhanced Curie temperature (T C). In addition to the Néel skyrmions observed in the temperature range of 250–340 K, we also detect type-I and -II Bloch-type skyrmionic bubbles in the temperature range of 100–200 K due to an enhanced magnitude of dipole-dipole interactions relative to the Dzyaloshinskii-Moriya exchange interaction. Self-intercalation is thus a highly interesting property of vdW magnets that considerably modifies their fundamental properties.